Liquidity risk and bank performance: an empirical test for commercial banks in Malaysia / Siti Maisarah Amran - Amran, Siti Maisarah (2018)
During the phenomenon of financial crisis in 1997 and 2008, heavy buying of U.S treasuries in 1997 was the option that world's sovereignties used as their global investments as the countries wish to stabilize the currencies in the first place. The involvement of International Monetary Fund (IMF) literally gave a big impact to the economy as they provided loans to stabilize back the economy and there were many countries that shows positive sign. The commercial banks' performance can be classified unknown before, during and after the crisis. The aim of this research is to study the relationship between banking characteristics with net interest margin in Malaysia. This research is conducted on a yearly basis and the period of the study is 21 years which starting from 1997 till 2017. Next, gross domestic product, capital adequacy ratio, bank size and inflation rate have been selected as the independent variables. This research also will be using four (4) commercial banks in Malaysia.